In vivo comparative evaluation of mineral trioxide aggregate and formocresol pulpotomy in primary molars: A 60-month follow-up study - Shivayogi M Hugar (Contemporary Clinical Dentistry, 2017)
Introduction: Pulpotomy is a regular procedure in the management of inflamed primary teeth. Diverse materials have been reviewed for the pulpotomy, some of them being formocresol, glutaraldehyde, ferric sulfate, and mineral trioxide aggregate (MTA). Aims: The aim was to evaluate and compare clinically and radiographically the effects of MTA as a pulp dressing after coronal pulp amputation (pulpotomy) in primary molars. Settings and Design: Sixty primary molars of thirty healthy children using split mouth design aged between 4 and 6 years were treated by pulpotomy technique. Subjects and Methods: Sixty primary mandibular molars of thirty healthy children aged between 4 and 6 years were treated by pulpotomy technique. The teeth on the right side were assigned to MTA (Group A) and the left side for the formocresol (Group B). The children were then examined clinically and radiographically every 6 months. Statistical analysis used: Chi-square test using the SPSS version 19.0 was used to compare between the two groups. Results: Results showed that both MTA and formocresol have the same outcome on the primary molars, with Chi-square value being 1.1483 (P ≥ 0.05). None of the teeth in any children in the study showed any clinical pathology. Conclusion: The principle conclusions of this study are that there are no significant differences in MTA and formocresol. The success rate of MTA and formocresol pulpotomy can be considered comparable till this therapy influences the development and growth of the permanent teeth.